Reframing Occidentalism: Purpose, Construction of Scientific Paradigms, and Reconstruction of Post-Orientalism Knowledge - Badarussyamsi, Badarussyamsi (Journal of Islamic Thought and Civilization, 2023)
The current study aimed to reaffirm the framing of Occidentalism as an academic discipline that has a more constructive value, rather than placing it solely as a form of euphoric criticism and resistance to Orientalism and the West. The decline of Occidentalism as an academic discipline has been caused by framing which narrows its intellectual activities and allows it to function only as a critique of Orientalism. Previous studies concluded that Occidentalism is only the anti-thesis of Orientalism, although how Occidentalism – as a scientific discipline – composes its scientific paradigm, is barely discussed. What does Occidentalism actually criticize and how does it construct its epistemology as an important scientific discipline? This question is important to elaborate on the existence of Occidentalism. The current research conducted an in-depth study of the opinions and arguments of scientists, such as Edward W. Said, Hassan Hanafi, Sayyid Qutb, and Seyyed Hossein Nasr. By investigating the domain of their views, especially on Orientalism and the West, critical and dialectical themes were also classified to find the epistemological construction of Occidentalism. The findings showed that Occidentalism has ontological, epistemological, and axiological constructs which dialectically reveal the weaknesses of Orientalism. However, a more exploratory and important finding is that the epistemological construction of Occidentalism is divided into four major dialectical streams. Firstly, the critique of civilizational values, secondly, revealing the ontological, epistemological, and axiological structures, thirdly, offering a balanced discipline of study, and fourthly the discovery of a new path for Western civilization.